Assessing the values and potentials of public art in campus public space - Albahori, Ainul Samihah; Ramlan, Annur Jalilah; Zakariya, Khalilah (2014)
Public art is an art form installed in public spaces for public view. Its existence in the public space is often perceived to enhance the landscape setting and spatial experience for people. The manifestation of public art may be associated with the culture and identity of an area to give a positive impact to the public. Nevertheless, there are also public art that has little relationship to its surrounding context and merely stands on its own. In Malaysia, public art practice has begun to transform the public realm through revitalizing urban public spaces. While it is common to find public art in urban spaces nowadays, however, the potential role of public art in the campus public space has not received much attention. The campus landscape plays an important role to the campus communities as a place where they dwell, interact, learn and gain various experiences. The campus spaces act as a ground where knowledge is disseminated and activities are conducted. This paper examines the values of public art in the IIUM campus public spaces and their potentials to play a greater role in creatively uplifting the campus landscape. The methods for this study were conducted through literature review, case study, observation and questionnaire survey among IIUM students, staffs and visitors. The first part of the findings discusses several types and functions of public art in campus public space based on the user needs and requirements. The second part of the findings reveals the values ascribed by the campus community towards the existing public art and potential forms of public art to be introduced in the campus landscape. This paper concludes that public art has potential to rejuvenate the IIUM campus image as 'Garden of Knowledge and Virtue' and improve peoples' experiences in creating a better living and learning environment, following certain considerations as discovered in the findings.